Postactivation Potentiation in Blood Flow–Restricted Complex Training. Issue 4 (April 2020) - Cleary, Christopher J.; Cook, Summer B.
Abstract : Abstract: Cleary, CJ and Cook, SB. Postactivation potentiation in blood flow–restricted complex training. J Strength Cond Res 34(4): 905–910, 2020—Complex training uses a high-load (HL) resistance exercise to elicit postactivation potentiation (PAP) that is typically observed through enhanced plyometric performance. Blood flow–restricted (BFR) resistance exercise uses low loads to induce similar muscular adaptations to HL resistance exercise; however, the efficacy and feasibility of BFR complex training are unknown. Fifteen college-aged men (mean ± SD ; age: 20.3 ± 0.9 years; relative back-squat one-repetition maximum [1RM]: 1.78 ± 0.3 kg·kg −1 ) with at least 2 years of resistance training experience completed 3 sessions: a familiarization session with 1RM testing, and 2 complex training sessions of 3 presquat vertical jumps (VJs), condition-specific back squats (HL: 5 repetitions at 85% 1RM, BFR: 30 repetitions at 30% 1RM), and a single postsquat VJ. Postactivation potentiation was calculated as (postsquat VJ height ÷ max presquat VJ height) [BULLET OPERATOR] 100. Electromyography (EMG) of the vastus lateralis and hamstrings was collected, quantified to root mean square values, and normalized to peak 1RM activity. Postsquat VJ height was significantly reduced in both conditions, and PAP did not occur because it was less than 100% (HL: 96.1 ± 5.1%, BFR: 90.8 ± 7.8%, p = 0.010). Vastus lateralis and hamstrings EMG amplitude was highest ( p < 0.001) in the HL condition. High-load and BFR complex training decreased subsequent VJ height in these individuals, and this might have been due to an ineffective complex training protocol and individual factors such as training status and relative strength.